Czech Castles and Chateaux: An Alternative Interpretation of a Phenomenon - Kurz, Michal; Pýcha, Čenek (Dějiny – teorie – kritika, 2022)
The paper identifies and examines several facets of the phenomenon of visiting castles and chateaux, which has continued to be a well-established and widely shared cultural practice in Czech society since the late 1940s. It demonstrates how this phenomenon can be interpreted in a historical perspective in the spirit of critical heritage studies. It also explores peculiarities and paradoxes of historical development, the consequences of which translate in many ways into the present state of the practice of visiting castles and chateaux.